Effect of soil solarization using LDPE - mulch on moisture conservation and soil temperature variation - ANU VARUGHESE; Dr. K. John Thomas (Guide) (Tavanur 1997 Kelappaji College of Agricultural Engineering and Technology)
Effect of soil solarization using LDPE - mulch on moisture conservation and soil temperature variation
Effect of soil solarization using LDPE - mulch on moisture conservation and soil temperature variation